Laboratornoe testirovanie vysokokvalificirovannych grebcov-kanoistov s pozicii prognozirovanija uspešnosti ich sorevnovatel'noj dejatel'nosti - Makarova, G. A.; Pogrebnoy, A. I.; Chernukha, S. M.; Karpov, A. A.; Kvashuk, P. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The prime objective of the paper was to determine diagnostic capabilities for conventional set of anthropometric and physio-logical parameters during perioical medical examination of well trained and elite canoeists in the context of forecasting success in their competitive activities within the selected season. Particular task of the study was to identify differences in anthropometric, strength, ergometric, gasometric, pulse and biochemical parameters in athletes classified as "successful" and "unsuccessful" subgroups (in terms of the level and stability of athletic achievements in the selected season) in the middle of preparatory phase and at the close of pre-competition phase within the annual training program. The data obtained show that in the middle of the preparatory phase well and highly trained canoeists performing with the desired results in competitive season are notable only for higher percentage of muscle mass and, as may be supposed, higher total physical performance. At the close of the pre-competition phase none of the ergometric, gasometric, hemodynamic and biochemical parameters registered during laboratory testing of the athletes have prognostic significance. As things stand today, only high tolerance of central nervous system's functional state, its psychoemotional component in particular (motivation to train, sleep, appetite), to exercise-induced metabolic shift and higher cortisol level in blood at the end of a week-long micro cycles serve as prognostically significant parameters for classification into "successful" subgroup regarding the level and stability of athletic achievementsin elite canoeists.